Automated pH Regulator For Freshwater Prawn With Analog pH Meter Pro - Nordin, E.S.M.; Abas, H.; Bakar, N.A.A. (International Journal of Human and Technology Interaction (IJHaTI), 2021)
In Malaysia, farmers faced the problems of prawn diseases which cause billions of USD in damage, along with the loss of prawn production. Farmers begin to wipe out from the prawn industry and investors are unwilling to finance prawn production. There will be a risk that it will decrease the productivity of Malaysia's prawn production due to the prawn affected by diseases. Research shows that an uncontrolled pH level in the prawn tank causes the prawn to be stressed and lower the prawn immunity system. As a result, diseases such as Early Mortality Syndrome (EMS), White Spot Syndrome Virus (WSSV), and Taura syndrome virus (TSV) can easily attack the prawn.  The existing water quality monitoring system lacks a complete solution from monitoring the pH level until autonomous remedial action is taken to control the pH level. When developing the system, no autonomous remedial action being taken to control when the pH level is out of range. Automated pH Regulator For Freshwater Prawn with Analog pH Meter Pro help farmers to monitor and control pH level in prawn tank. Logged data is stored in a personal computer for reference to prawn health. This paper proposes a conceptual framework with three (3) stages that consist of monitoring pH level with threshold data to determine pH level, provide autonomous remedial action to control the pH level in prawn tank, and logged data into a personal computer for reference. By having an Automated pH Regulator For Freshwater Prawn with Analog pH Meter Pro, immediate action can be carried out to save the prawn's life from diseases.